2022
DOI: 10.1097/cu9.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy during pregnancy: Outcomes and lessons learned over 4 decades at a tertiary center in Norway

Abstract: BackgroundThe management of suspected kidney stone disease in pregnancy is challenging. In cases of persistent flank pain and where investigations may have rendered equivocal results, ureteroscopy (URS) is a recognized diagnostic and therapeutic intervention. This study aimed to investigate the safety and outcomes associated with performing URS during pregnancy, as the technique has evolved over the past 4 decades at our center.Materials and MethodsWe performed a retrospective analysis of pregnant patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Improved ureteroscopes and vision have also improved the management of upper tract tumors. 82 , 83 While it also allows the treatment of high-risk patient groups such as in pediatric patients and during pregnancy, 84 , 85 perhaps future studies should also consider the cost and quality of life aspects of stone treatment. 86 , 87 …”
Section: Resultsmentioning
confidence: 99%
“…Improved ureteroscopes and vision have also improved the management of upper tract tumors. 82 , 83 While it also allows the treatment of high-risk patient groups such as in pediatric patients and during pregnancy, 84 , 85 perhaps future studies should also consider the cost and quality of life aspects of stone treatment. 86 , 87 …”
Section: Resultsmentioning
confidence: 99%
“…This includes the 4.9 Fr tapered tip of the Olympus URF‐P7. The smaller size has been found to translate to clinical advantages especially for negotiating access to the ureteric orifice in more challenging anatomy such as children and pregnancy 58,59 . That model also has a smooth bullet shape to it that is lacking in SU models.…”
Section: Arguments For Reusable Ureteroscopesmentioning
confidence: 99%
“…This includes the introduction of digital technology, optic systems and a wide selection of accessories that can be used 4,5 . As such, the selection of patient groups that can be safely treated has been expanded and now includes patients at the extremes of age, pregnancy and complex anatomy such as renal transplants 6–8 . Single use (SU) flexible ureteroscopes (also referred to as ‘disposable’) are another development that became commercially available in October 2015 9 .…”
Section: Introductionmentioning
confidence: 99%
“…While performing URS after the first trimester is preferred to minimize the risks associated with surgery and anesthesia, a retrospective study from a tertiary center demonstrated the absence of intraoperative or postoperative obstetric complications following URS performed in the first trimester. [48] The same study showed that URS may be performed safely during pregnancy with local anesthesia (2% lidocaine gel) and light sedation, which offers a useful alternative for patients in whom spinal anesthesia cannot be tolerated or is contraindicated and for patients who do not want to undergo general anaesthesia. [48]…”
Section: Managementmentioning
confidence: 99%
“…[48] The same study showed that URS may be performed safely during pregnancy with local anesthesia (2% lidocaine gel) and light sedation, which offers a useful alternative for patients in whom spinal anesthesia cannot be tolerated or is contraindicated and for patients who do not want to undergo general anaesthesia. [48]…”
Section: Managementmentioning
confidence: 99%